The Algorithmic Gatekeeper: Should AI Be Used in Emergency Triage? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
The Algorithmic Gatekeeper: Should AI Be Used in Emergency Triage? The emergency department (ED) is a high-stakes environment where rapid, accurate deci...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Machine Learning; Medical Ethics